Perception towards advertising on sports apparel among FSR students / Aiman Haqim Yahya - Yahya, Aiman Haqim (2018)
The purpose of this research study is to investigate the perception towards advertising on sports apparel among FSR students. 298 students from Faculty of Sports Science and Recreation were involved as the main respondent of this study. For the purpose of the study, the questionnaire was adopted and adapt from Shaouf, Lu & Li (2016). The differences of perception towards advertising based on gender showed there is significant difference based on gender on one of the three element of perception towards advertising, which is quality. For male, it is (M=4.09, p=0.009), meanwhile female it is (M=4.27, p=0.009). Based on the results, there was significant difference in perception towards advertising based on usage pattern which is quality. For daily usage, it is (M=4.23, p=0.009), meanwhile occasionally is (M=4.00, p=0.009). Lastly, for purchasing style, there is also significant difference for all three domains, which are design, quality and brand. For design, online store is (M=3.93, P=0.008) meanwhile retail shop is (M=4.27, p=0.008). For quality, online store is (M=3.94, p=0.0 16) meanwhile retail shop is (M=4.20, p=0.0 16) meanwhile for brand, online store is (M=3.88, p=0.007) and retail shop is (M=4.19, p=0.007). Overall, by identifying the perception towards advertising among them the result of the study will allow a reappraisal of how to improve advertising quality in the future.